The Method Afro-Brazilian cardio (The method series, 1993)
Let your body experience the energy of Afro-Brazilian moves to the uplifting beat of a live percussion band. Each of the three workouts takes you a step further toward a complete body toning experience. The rhythmic, low impact dance moves from Africa and Brazil work your entire body while energizing your mind.